Achieving Full Satisfaction: Revealing the Influence of the Quality of Information, Systems, and Application Services on Information System User Satisfaction - Prasojo, Luqman (Journal of Economicate Studies, 2023)
Influence testing is the goal of this study, by analyzing information quality, system quality, and application service quality to information system users. In today's digital era, information systems play an important role in increasing organizational efficiency and effectiveness. However, user satisfaction with the information system is an important benchmark that can affect the success of the implementation and acceptance of the system by its users. This study uses a quantitative approach using survey data collected from information system users. Survey data were analyzed using the regression analysis method to examine the relationship between the independent variables (information quality, system quality, and application service quality) and the dependent variable (system user satisfaction). This variable was adopted from the Information System Success model designed by DeLone and McLean in 2003 by using several required variables. The results of this study indicate that there is a significant positive effect of information quality on system user satisfaction. Information that is accurate, relevant, and easily accessible provides great benefits for users in using information systems. In addition, the quality of information also has a positive effect on system user satisfaction. The good performance, reliability, and speed of the system in processing user requests, enables users to achieve their goals more effectively and efficiently. Furthermore, application service quality also has a positive influence on system user satisfaction. Services that are responsive, accessible anytime and anywhere, friendly and professional provide a positive experience for users. This research provides important insights, especially for information system developers and application service providers to be able to consider that user experience and system user satisfaction are components that need to be prioritized. In facing increasingly fierce competition, service providers need to ensure that their information systems are able to provide good quality information, have reliable systems, and provide application services that meet user expectations. Thus, achieving full satisfaction is the goal of the organization to continue to improve, which in turn will increase the adoption and acceptance of information systems by users.